El régimen evocativo del ensayo fotográfico documental contemporáneo en las obras de Yael Martínez (México) y Franz Krajnik (Perú) - Larrabure Simpson, María Cecilia (2021)
This study aims to explain photography’s capacity to develop essayistic visual narratives that tend to create messages focused on photography’s evocative power rather than on its informative one, even when the matrix of such narratives is rooted in the document itself. These new visual narratives, based mainly on the sensorial power of photography and that have seen its production multiplied since the arrival of the 21st century, enable new ways of unraveling the image’s latent meanings, which cannot be seen, but can be intuited. The authors whose photo essays are analyzed in this article, organize the image’s visual elements in such way that when confronted with the spectator during the contemplative act, unveil, through evocation, photography’s multiple latent meanings such as, in these cases, pain, loss and emptiness, but also hope and resilience.